Women’s Efforts To Improve Their Economy Through Reading Access Among Religious Women’s Organisations - Soesantari, Tri (Opción, 2019)
The aim of this research is to learn how Aisyiyah’s members’ efforts in rela- tion to providing reading access has increased women’s economic enhance- ment. This study uses a qualitative approach with research subjects namely the two regional leaders (district or city level) in the Aisyiyah organisation in Banyuwangi District and Sidoarjo District. The results of the women’s efforts to improve their economic enhancement through their reading access has been assessed. The same thing also happened in Sidoarjo; they read literature to improve their knowledge and to increase their economic status by developing themselves in various industries such as batic, embroidery, culinary and so on.